Circadian Rhythm New Insights Into Physiological and Pathological Implications - Manuela Drăgoi, Cristina; Crenguța Nicolae, Alina; Dumitrescu, Ion-Bogdan (IntechOpen, 2022)
This book provides a systematic and updated scientific perspective on the physiology of circadian rhythms, the molecular mechanisms of circadian entrainment, the pharmacological features derived from these signalling pathways, and their clinical outcomes. It offers a comprehensive perspective on the chronobiological impact on normal developmental processes, disruptive events that modulate the occurrence of diverse imbalances that sometimes imply disease, and the increasing importance of circadian rhythms in drug delivery.